A161 - study of CNT composite - Teo, Brannon Zi Wei (2014)
Carbon Nanotubes (CNT) have many useful applications and uses due to their unique inherent properties. By combining these properties with other various substances and materials, it is possible to achieve a nanocomposite with the desired properties for its intended use in engineering. These can range from high strength high ductility CNTs, Good thermal conductance, and optical properties such as photoluminescence to name a few.